Modeling of a nonlinear deformation of orthotropic cylindrical shells with a hole with regard for the eccentricity of its reinforcement - Chernyshenko, I. S.; Komarchuk S. М.; Maksimyuk, V. A.; Storozhuk, E. A. (Reports of the National Academy of Sciences of Ukraine, 2016)
The technique of numerical analysis of a stress-strain state of flexible orthotropic cylindrical shells reinforced by a circular hole under the influence of a static load is developed. The proposed technique is based on using the same ratio in the simulation of deformation of a shell and a reinforcement. For a shell loaded by a uniform internal pressure, the effect of the eccentricity of a reinforcement on the distribution of stresses, strains, and displacements in the area of their concentration is studied.